Morphology, Genesis and Classification of Soils of Central Research station Farm, Dr. Punjabrao Deshmukh Krishi Vidyapeeth, Akola - Suresh Kumar, Y.S. (Journal of Soil and Water Conservation, 2022)
Soils of central research farm Dr. P.D.K.V., Akola were studied by taking representative pedons one each in oil seed, sorghum, cotton and LRM unit. The soils are very deep in pedons 2, 3 and 4 except pedon 1 deep. The soils are clay to clay loam, moderately well drained and calcareous. The soil pH varies from 7.9 to 8.8 and EC 0.18 to 0.49 dS ny’ with fairly high CEC and base saturation range from 82 to 92% respectively. These soils are low to medium in organic carbon and available N, low in available P2O5 and high in available K2O. Taxonomically the soils were classified as: Pedon 1 — Vertic Ustochrepts, Pedon 2 and 3 Typic Chromusterts and Pedon 4-Udic Chromusterts